Ответы и объяснения

2013-06-03T11:57:25+00:00

y=2+5x-\frac{2}{3}x\sqrt{x}\\y'=(2+5x-\frac{2}{3}x\sqrt{x})'=5-((\frac{2}{3}x)'*(\sqrt{x})+(\frac{2}{3}x)*(\sqrt{x})')=\\=5-\frac{2\sqrt{x}}{3}-\frac{2x}{3*2\sqrt{x}}=5-\frac{2\sqrt{x}}{3}-\frac{x}{3\sqrt{x}}

 

y'=0

[tex]5-\frac{2\sqrt{x}}{3}-\frac{x}{3\sqrt{x}}=0\ \ \ \ \ \ \ \ \ |*3\sqrt{x}\neq0\\15\sqrt{x}-2x-x=0\\15\sqrt{x}=3x\\225x=9x^2\\9x^2-225x=0\\x(9x-225)=0\\9x-225=0\\x=25[/tex]

x=0 небудет удовлетворять, т.к. в знаменателе получится ноль.

 

x=25 - точка максимума